On the exponential dichotomy of pulse evolution systems - Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The equivalence of regularity and exponential dichotomy is established for linear pulse differential equations with unbounded operators in a Banach space. The separatrix manifolds of a linear pulse system exponentially dichotomous on a semiaxis are studied in a finite-dimensional space. The conditions of weak regularity of this system are given.